Angiotensin II: a new therapeutic option for vasodilatory shock - Bussard RL; Busse LW (Dove Medical Press, 2018)
Rachel L Bussard,1 Laurence W Busse2,3 1Critical Care Pharmacy Specialist, Department of Pharmacy, Emory St Joseph’s Hospital, Atlanta, GA, USA; 2Department of Critical Care, Emory St Joseph’s Hospital, Atlanta, GA, USA; 3Division of Pulmonary, Critical Care, Allergy and Sleep Medicine, Department of Medicine, Emory University, Atlanta, GA, USA Abstract: Angiotensin II (Ang II), part of the renin–angiotensin–aldosterone system (RAS), is a potent vasoconstrictor and has been recently approved for use by the US Food and Drug Administration in high-output shock. Though not a new drug, the recently published Angiotensin II for the Treatment of High Output Shock (ATHOS-3) trial, as well as a number of retrospective analyses have sparked renewed interest in the use of Ang II, which may have a role in treating refractory shock. We describe refractory shock, the unique mechanism of action of Ang II, RAS dysregulation in shock, and the evidence supporting the use of Ang II to restore blood pressure. Evidence suggests that Ang II may preferentially be of benefit in acute kidney injury and acute respiratory distress syndrome, where the RAS is known to be disrupted. Additionally, there may be a role for Ang II in cardiogenic shock, angiotensin converting enzyme inhibitor overdose, cardiac arrest, liver failure, and in settings of extracorporeal circulation. Keywords: catecholamine resistance, refractory shock